PENGARUH KARAKTERISTIK PERUSAHAAN DAN SALES GROWTH TERHADAP TAX AVOIDANCE (Studi Kasus pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di BEI tahun 2013 – 2016) - Puji Lestari, Fadjar Harimurti & Suharno (Universitas Slamet Riyadi, 2019)
The purpose of this research is to find out the influence of corporate characteristics and Sales Growth on tax avoidance. This research was conducted on manufacturing sector food and beverage companies in Indonesia Stock Exchange (IDX) 2013 - 2016. The population are 16 companies and the samples are 11 manufacturing sector food and beverage companies which are listed in IDX and the sample collection technque has been done by using purposive sampling. The independent variables consist of corporate characteristics and Sales Growth, the dependent variable in this research is tax avoidance. The analysis technique employs multiple linear regressions analysis. data were analized using SPSS software version 21. The result of the research shows that size, audit committee and sales growth variable has significant influence on tax avoidance. Variables independen commissioner do not have any significant influence on corporate tax avoidance. Keywords: Size, independen commissioner, audit committee, sales growth, tax avoidance.